Genetic and demographic founder effects have long‐term fitness consequences for colonising populations. (1st February 2017) - Szűcs, Marianna; Melbourne, Brett A.; Tuff, Ty; Weiss‐Lehman, Christopher; Hufbauer, Ruth A.
Abstract: Colonisation is a fundamental ecological and evolutionary process that drives the distribution and abundance of organisms. The initial ability of colonists to establish is determined largely by the number of founders and their genetic background. We explore the importance of these demographic and genetic properties for longer term persistence and adaptation of populations colonising a novel habitat using experimental populations of Tribolium castaneum . We introduced individuals from three genetic backgrounds (inbred – outbred) into a novel environment at three founding sizes (2–32), and tracked populations for seven generations. Inbreeding had negative effects, whereas outbreeding generally had positive effects on establishment, population growth and long‐term persistence. Severe bottlenecks due to small founding sizes reduced genetic variation and fitness but did not prevent adaptation if the founders originated from genetically diverse populations. Thus, we find important and largely independent roles for both demographic and genetic processes in driving colonisation success.